Purification and properties of the mini-F plasmid-encoded E protein needed for autonomous replication control of the plasmid. - Tokino, T (1986)
Mini-F plasmid encodes a protein, E protein, that is indispensable for its autonomous replication. We have constructed a plasmid that overproduces the E protein and have purified the protein to apparent homogeneity. Using nitrocellulose filter binding and nuclease digestion assays, we demonstrated that the E protein binds to three unique regions of the mini-F DNA sequence: the replication origin (ori2) and an incompatibility locus (incB), another incompatibility locus (incC), and the promoter for the E gene. These binding sites have a common 8-base-pair sequence. These findings suggest the direct role of the E protein in initiation of mini-F replication and copy number control. They are also in line with the in vivo evidence that the incompatibility phenotype caused by incB and incC DNA is due to titration of a factor(s) indispensable for replication and that the production of the E initiator protein of the mini-F plasmid is under autoregulatory control.